RESPON PADI IR64 TERHADAP PEMBERIAN Zn DENGAN PENGATURAN JADWAL TANAM DI LAHAN PASANG SURUT - Tri Anditasari; Ardian '; Idwar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
In rice cultivation in tidal land are inundated land constraints. Under conditions of stagnant nutrient zinc is not available and the seedlings will experience stress submerged. This research aimed to evaluate the response of paddy ups and downs against the granting of multiple doses of zinc and setting planting schedule. The experiment was conducted in Teluk Sungkai, Kuala Cenaku in September 2014 - January 2015. The experiment was arranged in completely randomized factorial design with two factors and three replications. The first factor is the dose of zinc: 30 kg ZnSO4/ha, 40 kg ZnSO4/ha, and 50 kg ZnSO4/ha. The second factor is planting schedule: 5 days after the large tidal, 10 days after the large tidal, and 15 days after the large tidal. Based on this research the best dosage of zinc is 40 kg ZnSO4/ha and schedule 15 days after the large tidal better than the other planting schedule for paddy’s growth and production.   Keywords: rice, zinc, land tidal